The effect of application of learning start with a question concept photosynthesis on students' cognitive learning outcomes, critical thinking and scientific work IPA SMP - Riyanty Lololuan; Hasan Tuaputty; Pamella Mercy Papilaya (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2023)
One of the roles of the teacher in implementing an education is by using a learning starts with a question method. The learning starts with a question method is a method in which students are directed to learn independently by making questions based on the reading provided by the teacher. This study aims to see the effect of applying learning starts with a question on photosynthesis material on students' cognitive learning outcomes, critical thinking, and scientific work in class VIII SMP Negeri 15, SMP Negeri 7, SMP Kristen Kusu-Kusu, SMP Negeri 11, and SMP Negeri 4. Research data was analyzed quantitatively using descriptive and inferential statistics in the form of anacova analysis to see the effect of applying learning starts with a question on students' cognitive learning outcomes, critical thinking, and scientific work. The results of this study indicate that there is an effect of the application of the learning starts with photosynthesis material on students' cognitive learning outcomes, critical thinking, and scientific work.